Perceived Stress and Avoidant Coping Moderate Disordered Gambling Among Emerging Adults in Vietnam. (March 2013) - Lostutter, Ty W.; Larimer, Mary E.; Neighbors, Clayton; Kaljee, Linda M.
Gambling research conducted in Asia has been limited, despite a continued growth of the gambling industry within the region. Outside Asia, research suggests emerging adults have high rates of gambling behavior and experience serious consequences. The current study examines gambling behavior within an emerging adult (ages 16-24) population in Vietnam. The study evaluates gambling and tests a moderation model of stress and coping in relation to gambling. The rate of disordered gambling in this sample using the South Oaks Gambling Screen (SOGS, 3+) is 15%, slightly higher in comparison to samples of similar aged youth in other countries. Results also indicate avoidant coping moderated the relationship between gambling frequency and gambling problems, such that frequency was more strongly associated with gambling problems among individuals higher in avoidant coping. Etiological and epidemiological implications are discussed in the context of a developmental perspective on disordered gambling among Vietnamese emerging adults.